Fermented total mixed ration enhances nutrient digestibility and modulates the milk components and fecal microbial community in lactating Holstein dairy cows - Wang, Lijun; Jin, Sanjun; Wang, Ping; Li, Xinxin; Liu, Chaoqi; Sun, Siying; Zhang, Guangning; Chang, Juan; Yin, Qingqiang; Zhang, Haiyang; Zhu, Qun (Frontiers in Veterinary Science, 2024)
Fermented total mixed ration (FTMR) is an effective method of preserving high-moisture byproducts with higher aerobic stability after fermentation. FTMR has the potential to fulfill the daily nutritional requirements of cattle and enhance their production performance. The objective of this research was to examine the influence of fermented total mixed ration (FTMR) on lactation performance, total tract apparent digestibility, fecal microbiota communities, and fermentation profiles in lactating dairy cows. . A total of 12 cows were randomly assigned into two groups: the TMR group and the FTMR group. The TMR group was fed a total mixed ration (TMR) diet, and the FTMR group was fed an FTMR diet. The FTMR did not impact milk yield in dairy cows despite a decrease in dry matter intake, which increased the efficiency of the feed. In contrast to that in the TMR group, the milk fat content in the FTMR group was greater. The FTMR group showed greater digestibility of neutral detergent fiber (NDF), organic matter (OM), dry matter (DM), crude protein (CP), and acid detergent fiber (ADF) in the total digestive tract than did the TMR group. The FTMR increased the concentration of butyrate in the fecal matter and reduced the pH of the feces. The Chao1, ACE, and Shannon indices of the archaeal community in dairy cow feces were significantly greater in those fed the FTMR than in those fed the TMR. LefSe analysis revealed higher levels of Oscillospira, Lactobacillus, Prevotella, and Dehalobacterium in the feces of dairy cows fed the FTMR than in those fed the TMR. However, the abundances of Roseburia, rc4-4, Bulleidia and Sharpea exhibited the opposite trend. The abundances of Halobacteria, Halobacteriales, and Halobacteriaceae, which are biomarkers for distinguishing fecal archaea in the TMR from the FTMR, were substantially greater in the feces of dairy cows that consumed the TMR than in those that consumed the FTMR. Therefore, FTMR can improve the milk fat content, total tract apparent feed digestibility efficiency, and diversity of archaea in the feces. Additionally, this work provides a theoretical basis for the feasibility of FTMR feeding for dairy cows.